2021
DOI: 10.1002/cjp2.211
|View full text |Cite
|
Sign up to set email alerts
|

CRLF2 and IKZF1 abnormalities in Mexican children with acute lymphoblastic leukemia and recurrent gene fusions: exploring surrogate markers of signaling pathways

Abstract: The gene fusions BCR‐ABL1, TCF3‐PBX1, and ETV6‐RUNX1 are recurrent in B‐cell acute lymphoblastic leukemia (B‐ALL) and are found with low frequency in coexistence with CRLF2 (cytokine receptor‐like factor 2) rearrangements and overexpression. There is limited information regarding the CRLF2 abnormalities and dominant‐negative IKZF1 isoforms associated with surrogate markers of Jak2, ABL, and Ras signaling pathways. To assess this, we evaluated 24 Mexican children with B‐ALL positive for recurrent gene fusions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
2
1
0
Order By: Relevance
“…In addition to this, we observed a high frequency of iAMP21 in our patients, frequently associated with P2RY8::CRLF2 deletion, as well as the presence of IKZF1 abnormalities. Collectively, our results appear consistent with the ones previously reported in the literature [ 20 , 35 , 36 ]; hence, the detection of these lesions must be considered in the routine screening of genetic abnormalities in pre-B ALL in Mexican patients. Finally, as all these abnormalities require high-risk therapy regimens, which include the use of specific inhibitors, a mandatory routine identification of this genetically heterogeneous entity will have a positive contribution to the overall survival of Mexican patients [ 1 , 11 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition to this, we observed a high frequency of iAMP21 in our patients, frequently associated with P2RY8::CRLF2 deletion, as well as the presence of IKZF1 abnormalities. Collectively, our results appear consistent with the ones previously reported in the literature [ 20 , 35 , 36 ]; hence, the detection of these lesions must be considered in the routine screening of genetic abnormalities in pre-B ALL in Mexican patients. Finally, as all these abnormalities require high-risk therapy regimens, which include the use of specific inhibitors, a mandatory routine identification of this genetically heterogeneous entity will have a positive contribution to the overall survival of Mexican patients [ 1 , 11 ].…”
Section: Discussionsupporting
confidence: 92%
“…The primer sets and probes for the genes of this assay are presented in Supplementary Table S3 . The cut-off value for the expression of each transcript was based on the analysis of quartiles and was set as previously described [ 36 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of B-cell (88.7%) in our study is higher than the reported previously in MC (73.2-85.1%) (3,15,24,132) but is similar to worldwide reported frequencies (80-92%) (111,112), except to that reported in Asian countries (92.7%) (132). These differences could be associated with the genetic profile of our population with B-cell, as reported in a study by , who report a high frequency (54.1%) of dominant-negative IKZF1 isoform transcripts in a pediatric population from a single medical institution (133). One of the reasons why there is a greater frequency of B-cell among Hispanics may be its relationship with IKZF1 and ARID5B, which have also been reported more frequently in Hispanics.…”
Section: Al Incidence Trendssupporting
confidence: 87%